Migraine-Asthma Comorbidity and Risk of Hypertensive Disorders of Pregnancy. (13th August 2012) - Czerwinski, Stefanie; Gollero, Jolana; Qiu, Chunfang; Sorensen, Tanya K.; Williams, Michelle A.
Abstract : Background . To evaluate the association of migraine and asthma and to estimate the risk of hypertensive disorders of pregnancy in relation to maternal comorbid migraine and asthma. Methods . Reproductive age women (N = 3.731 ) were interviewed during early pregnancy. At the time of interview, we ascertained participants' migraine and asthma status. From medical records, we collected information to allow the diagnosis of pregnancy-induced hypertension (PIH) and preeclampsia. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using logistic regression procedures. Results . After adjusting for confounders, migraineurs had 1.38-fold increased odds of asthma as compared with nonmigraineurs (95% CI 1.09–1.38). The odds of hypertensive disorders of pregnancy were highest among women with comorbid migraine-asthma. The ORs for PIH preeclampsia and the two disorders combined were 2.53 (95% CI 1.39–4.61), 3.53 (95% CI 1.51–8.24), and 2.64 (95% CI 1.56–4.47), respectively, for women with comorbid migraine-asthma as compared with those who had neither disorder. Conclusion . These findings confirm prior reports and extend the literature by documenting particularly high odds of pregnancy-induced hypertension and preeclampsia among women with comorbid migraine-asthma. Increased knowledge about the prevalence and sequelae of comorbidities during pregnancy may lead to improved symptom management and perinatal outcomes.